2023
DOI: 10.3390/clinpract13010029
|View full text |Cite
|
Sign up to set email alerts
|

Notalgia Paresthetica Review: Update on Presentation, Pathophysiology, and Treatment

Abstract: Purpose of Review: Notalgia paresthetica (NP) is a chronic cutaneous neuropathy primarily characterized by localized pruritus and associated dysesthesias, including sensations of pain, numbness, and tingling. The sensory neuropathy characteristic of NP is thought to result from spinal nerve entrapment caused by degenerative changes in the spine or musculoskeletal compression. This review summarizes the current medical literature with a focus on the past five years regarding NP, its pathophysiology, presentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Hence, it is imperative to correctly recognize and treat NP, particularly as it is reported to be underdiagnosed in several cases 27 . The exact etiology of NP is still uncertain; however, it is suggested that a multifactorial process involving muscle impingement, increase in dermal innervation, and any spinal pathology may contribute to the progression of this condition by affecting the posterior cutaneous branches of T2–T6 spinal nerves 28 . Following chronic rubbing and scratching to relieve the discomfort, hyperpigmented patches and lichenification appear on the affected part of the back.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it is imperative to correctly recognize and treat NP, particularly as it is reported to be underdiagnosed in several cases 27 . The exact etiology of NP is still uncertain; however, it is suggested that a multifactorial process involving muscle impingement, increase in dermal innervation, and any spinal pathology may contribute to the progression of this condition by affecting the posterior cutaneous branches of T2–T6 spinal nerves 28 . Following chronic rubbing and scratching to relieve the discomfort, hyperpigmented patches and lichenification appear on the affected part of the back.…”
Section: Discussionmentioning
confidence: 99%
“… 27 The exact etiology of NP is still uncertain; however, it is suggested that a multifactorial process involving muscle impingement, increase in dermal innervation, and any spinal pathology may contribute to the progression of this condition by affecting the posterior cutaneous branches of T2–T6 spinal nerves. 28 Following chronic rubbing and scratching to relieve the discomfort, hyperpigmented patches and lichenification appear on the affected part of the back. Considering dermatological or neuromuscular aspects of NP, clinicians consider various therapeutic strategies to alleviate clinical signs and symptoms with different levels of success.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we had a patient who underwent almost all treatment modalities. NP, like many treatment-resistant cases, is a disease without mortality but can adversely affect patients' quality of life [ 21 ].…”
Section: Dıscussıonmentioning
confidence: 99%
“…Notalgia paresthetica (NP) is a chronic cutaneous neuropathy characterized by localized pruritus and associated pain, numbness, and/or paresthesia, affecting the medial or inferior scapular border [1]. It is classified as a type of neuropathic itch, which is an itch caused by a lesion of or disease of the somatosensory nervous system [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is classified as a type of neuropathic itch, which is an itch caused by a lesion of or disease of the somatosensory nervous system [2]. NP is often associated with degenerative changes in the cervical and/or thoracic spinal joints, yet definitive mechanisms leading to pruritus have not been elucidated [1,3]. In addition, treatment for NP remains underexplored [1].…”
Section: Introductionmentioning
confidence: 99%